The Effect of Digital Leadership on MSME Performance through Digital Transformation Readiness - Ahmad Mukhlis; Khaeruman Khaeruman (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Businesses increasingly face pressure to adopt digital technologies to remain competitive. This study aims to examine the effects of digital leadership and digital transformation readiness on MSME performance, with digital transformation readiness as a mediating variable in MSMEs in Serang City. The study employed a quantitative survey approach. Data were collected from 120 MSMEs using structured questionnaires and analyzed with SEM-PLS. The results showed that digital leadership positively and significantly affects MSME performance and digital transformation readiness. Digital transformation readiness also has a positive and significant effect on MSME performance and serves as a significant mediator between digital leadership and performance. This indicates that enhancing MSME performance depends not only on leaders’ ability to utilize digital technology but also on organizational readiness to integrate it across business processes. The study contributes theoretically to understanding digital leadership and transformation in MSMEs and offers practical guidance for policymakers and business actors to strengthen digital capacity, supporting adaptive and competitive MSME development in the digital economy era.